SYSTEMATIC LITERATURE REVIEW (SLR): NUCLEAR POWER PLANTS - Muhammad Reza Maulana Aliva; Nofi Yendri Sudiar; Hamdi Hamdi (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2023)
Nuclear Power Plant (NPP) is a thermal power plant using one or several nuclear reactors as its heat source. NPP uses radioactive materials such as uranium as the heat source by utilizing fission reactions. The fission reaction produces enormous heat energy. Currently, there are many studies on NPPs, ranging from technological developments to the environmental impact of the NPP itself. This study aims to identify research developments on nuclear power plants from around the world obtained from relevant international journals in 2017-2023. The method used in this study is the Systematic Literature Review (SLR) method. The SLR method is used to identify, review, evaluate, and conclude all available research with interesting topic areas, with specific relevant research questions. Data were obtained by searching journals with Harzing's Publish or Perish application from the Scopus journal database. There are 191 journals with the keyword